Antara Idealisme dan Pragmatisme: Ketegangan Antara Kedaulatan Rakyat dan Pengendalian Partai Politik dalam Demokrasi Perwakilan Indonesia - Amirul Hamdan Permana; Rafif Alwy Widianto (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the persistent tension between the ideal of people’s sovereignty and the pragmatic dominance of political party control within Indonesia’s representative democracy. Rooted in the constitutional mandate that sovereignty resides in the people, the analysis investigates how institutional mechanisms, such as parliamentary thresholds, candidate selection systems, and party discipline, mediate or constrain that sovereignty. Employing a qualitative normative-analytical method supported by empirical data from the General Elections Commission (KPU), Kompas Research and Development, and the Indonesia National Survey Project (INSP), the study critically assesses how legal structures and political behavior interact to shape democratic legitimacy. The findings reveal that electoral thresholds, while justified as stabilizing instruments, have systematically excluded millions of votes from legislative representation, as evidenced by the 17.3 million “wasted votes” recorded in the 2024 election. Simultaneously, persistent low public trust in political parties, averaging between 44% and 55% from 2017 to 2023, demonstrates a widening distance between citizens and party institutions. The discussion highlights that these patterns perpetuate a pragmatic logic of governance that prioritizes stability, patronage, and coalition survival over inclusivity and accountability. Although reform efforts, such as judicial scrutiny of threshold policies and calls for internal party democratization, indicate ongoing attempts to realign practice with constitutional ideals, their impact remains limited by entrenched elite interests. Ultimately, the study argues that Indonesia’s democratic consolidation depends on recalibrating the institutional balance between representation and control, ensuring that sovereignty is not merely procedural but substantively exercised by the people..